LIQUID LIQUID EQUILIBRIA OF THE WATER + ACETIC-ACID + CYCLOHEXYL ACETATE TERNARY - (:unkn) unknown (AMER CHEMICAL SOC, 1991)
Liquid-liquid equilibria for the water + acetic acid + cyclohexyl acetate system were measured at 298.16 +/- 0.20, 308.16 +/- 0.20, and 318.16 +/- 0.20 K. Tie-line compositions were correlated by the reduced Elsen-Joffe equation. Reliability of data was ascertained through Othmer-Tobias plots. Distribution coefficients and separation factors were evaluated over the immisicibility region, and it is concluded that the high-boiling solvent, cyclohexyl acetate, is a suitable separating agent for dilute aqueous acetic acid solutions. In addition, the temperature dependence of solubility and tie-line compositions is insignificant from 298 to 318 K, except at very low acetic acid concentrations.